2017
DOI: 10.22598/mt/2017.29.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Marketing in Comparison With Other Forms of Marketing in the Slovak Banking Sector

Abstract: Purpose -Social media have become an important marketing tool in recent years, used for marketing purposes by Slovak banks besides other forms of communication. A comparison of social media marketing perception by banks' customers on the Slovak market with other forms of marketing, examined across age groups, will be the main aim of this paper.Design/Methodology/Approach -This investigation was conducted using a questionnaire survey with self-assessment statements, rated on a fi ve-point Likert scale to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…For example, based on the example of a large bank in Kuwait, Roumieh et al (2018) showed how e-marketing could be implemented more effectively to attract new customers and maintain the existing ones by critically assessing the viability of e-marketing strategies for the promotion of Islamic banking. Research on perceptions of marketing in social media and its comparison with the perception of other marketing forms used in the Slovak banking market, taking age differences into account, was undertaken by Vejačka (2017). Additionally, Al-alak (2014) describes the impact of marketing activities on the quality of relationships between clients and employees in the Malaysian banking sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, based on the example of a large bank in Kuwait, Roumieh et al (2018) showed how e-marketing could be implemented more effectively to attract new customers and maintain the existing ones by critically assessing the viability of e-marketing strategies for the promotion of Islamic banking. Research on perceptions of marketing in social media and its comparison with the perception of other marketing forms used in the Slovak banking market, taking age differences into account, was undertaken by Vejačka (2017). Additionally, Al-alak (2014) describes the impact of marketing activities on the quality of relationships between clients and employees in the Malaysian banking sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is not to say that marketers ignore users older than 30. However, when banks and financial institutions attempted to use social media for marketing (Vejačka, 2017), they targeted older customers, and that did not pay off, as older generations were not that interested in such social media marketing activities. Younger generations are much easier to interact with through social media, since they also use it as the primary tool to stay informed about new products, services and the experience of others.…”
Section: Social Media Influencersmentioning
confidence: 99%
“…running an online financial literacy programme for high school students). However, empirical evidence is less encouraging regarding banks’ marketing efforts on social media (Rinaldi, 2015; Vejaĉka, 2017). Moreover, scholarly research on banks’ social media marketing is still limited and tends to focus on the motivators of, and barriers to, engaging in social media marketing (Mitic and Kapoulas, 2012), the effect of social media marketing on customer loyalty (Laksamana, 2018) and effective segmentation strategies for social media marketing (Durkin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%